Self Regulation Student of Memorizing Al-Qur’an in Ma’had Al-Muqoddasah Litahfidzil Qur’an Nglumpang Mlarak Ponorogo 2018-2019 - Abu Darda; Rasul Uddin (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2019)
Memorizing Al-Qur'an is not as easy as flipping a hand, but also requires along process involving time, effort, and even costs. said the process is not easybecause it has to memorize the contents of Al-Qur'an with a very large quantityconsisting of 144 letters, 6.236 verses, 77.439 words, 323.015 letters and theprocess of memorizing Al- Qur'an does not only involve cognitive parts, butmemorizers of Al-Qur’an also have good self-regulation in order achieve their goalsin reciting Al-Qur’an. Quran memorizer in addition to requiring adequate cognitive,Quran memorization activities also require determination and a straight forwardintention, it takes a hard effort, inner birth readiness, willingness, and strict selfregulation.This research aims to know (1) the intrapersonal self-regulation of thestudent memorizing Qur’an, (the interpersonal self-regulation of the studentmemorizing Al-Qur'an, and finally what is the meta-personal self-regulation ofstudent memorizing Al-Qur'an. This research is qualitative research, researchers usethe phenomenological paradigm, data collection techniques in this study usinginterviews, observation, and documentation. This study uses phenomenologicalanalysis. The results of this study indicate that the intrapersonal regulation ofstudent memorizing Al-Qur'an is having the purpose of memorizing Al-Qur'an,efforts to prevent and regulate motivation, have a strategy in memorizing andmurojaah (repeatition), and finding ways to resolve obstruction in memorizing theQur'an.